Bodies out of place: Black queer students negotiating identity at the University of Cape Town - Boonzaier, F.; Mhkize, L. (South African Journal of Higher Education, 2018)
The issue of racial identity and belonging appears to be foregrounded in current struggles around the transformation of higher education in South Africa. However, current debates about belonging as well as critiques of the masculinist nature of sectors of the student movement have drawn stark attention to the complexities of subjectivity. Intersectional subjectivities have been highlighted. This paper attends to the narratives of seven black queer students and their negotiations of identity at an historically white university in South Africa amid struggles around transformation/decolonisation. We employ the Photovoice method where participants produce photo-narratives around their identities as black queer persons. Our analysis reveals not only the extent to which participants’ experiences illustrate their struggles around belonging in a space not historically ‘theirs’ but also the extent to which their narratives are potentially transformative and challenge representations of them and their lives.